2017
DOI: 10.1016/j.cbpa.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in developing selective inhibitors of protein methyltransferases

Abstract: Mounting evidence suggests that protein methyltrans•ferases (PMTs), which catalyze methylation of histone as well as non-histone •proteins, play aa crucial role in diverse biological pathways and human• diseases. In particular, PMTs have been recognized as major players in •regulating gene expression and chromatin state. There has been an increasingly growing• interest in these enzymes as potential therapeutic targets and over the past two years tremendous progress has been made in the discovery of selective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…To better assess the therapeutic relevance of PRMT5 targeting in TNBC, we next examined the effect of PRMT5 inhibition on a panel of breast cell lines using the PRMT5specific inhibitor EPZ015666. 13,14,27 First, we confirmed that EPZ015666 inhibits PRMT5 activity by analyzing PRMT5specific methylation marks on histones H3 (H3R8me2s) and H4 (H4R3me2s) ( Figure 3A; Figure S5). We then conducted a cell viability assay on 13 breast cell lines, comprising eight TNBC-derived cell lines (ER-/PR-/HER-) from the different TNBC molecular subtypes defined by Lehmann 2 (Table S3), but also one ER+ (MCF-7), two ER−/HER2+ (HCC1954, SKBR3), and two non-tumorigenic mammary cell lines (MCF-10A, MCF-12A), for comparison purposes.…”
Section: Pharmacological Inhibition Of Prmt5 Impairs Breast Cancer mentioning
confidence: 55%
See 3 more Smart Citations
“…To better assess the therapeutic relevance of PRMT5 targeting in TNBC, we next examined the effect of PRMT5 inhibition on a panel of breast cell lines using the PRMT5specific inhibitor EPZ015666. 13,14,27 First, we confirmed that EPZ015666 inhibits PRMT5 activity by analyzing PRMT5specific methylation marks on histones H3 (H3R8me2s) and H4 (H4R3me2s) ( Figure 3A; Figure S5). We then conducted a cell viability assay on 13 breast cell lines, comprising eight TNBC-derived cell lines (ER-/PR-/HER-) from the different TNBC molecular subtypes defined by Lehmann 2 (Table S3), but also one ER+ (MCF-7), two ER−/HER2+ (HCC1954, SKBR3), and two non-tumorigenic mammary cell lines (MCF-10A, MCF-12A), for comparison purposes.…”
Section: Pharmacological Inhibition Of Prmt5 Impairs Breast Cancer mentioning
confidence: 55%
“…Despite considerable improvement in breast cancer therapeutic management, no targeted therapy yet exists for the treatment of TNBC, and this breast cancer subtype remains a challenge for oncologists. PRMTs have recently received considerable attention as potential therapeutic targets in various types of cancer, and several specific PRMT inhibitors have recently been described . The present study suggests a promising therapeutic potential for PRMT5 targeting in a subset of TNBC, using the small‐molecule inhibitor EPZ015666 .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Epigenetic drug development targeting PRMTs is focused on the reversibility of epigenomic modifications through targeted inhibition of PRMT enzymes. Fortunately, there are sufficient structural distinctions that tolerates and enables selective targeting of PRMTs (Richon et al 2011) using small-molecule inhibitors, creating desirable targets for therapeutic exploitation (Kaniskan & Jin 2017, Copeland 2018. Moreover, the potential translational outcomes associated with the tractable PRMT family are underscored by the list of epigenetic enzyme inhibitors undergoing appraisal in pre-clinical and clinical trials as novel cancer therapies (Hamamoto & Nakamura 2016, Oh et al 2017.…”
Section: Introductionmentioning
confidence: 99%